Racine and Seneca - Tobin, Ronald W., 1936- (North Carolina studies in the Romance languages and literatures, 2018)
This study brings to light the significant and long-obscured influence of the Roman dramatist and philosopher, Seneca, on the works of Racine. After describing the positive characteristics of Senecan tragedy and the crucial role it played in French drama from Jodelle through Corneille, Ronald W. Tobin analyzes Racine's unique adoption and absorption of Senecan material into his own plays, thereby extending the dimensions of his dramatic art. In the book's Conclusion, some theories are advanced for Racine's well-known silence about his debt to Seneca.